Lift-off of multiple particles in a narrow channel. (November 2020) - Maitri, R.V.; Padding, J.T.; Kuipers, J.A.M.; Peters, E.A.J.F.
Highlights: Analysis of mono-sized and equal density spheres in a narrow channel. Particle-resolved 3D Computational Fluid Dynamics of a particle-liquid system. Simulation results for a range of Archimedes and shear Reynolds numbers. Results summarized by a relation between the solids volume fraction, Ar and Res . Abstract: In this work, we perform simulations of particle laden flow in a wide and long narrow channel in a Newtonian fluid. Simulations are performed for mono-sized and equal density spheres with varying Archimedes and Reynolds number. In the simulations, different phases of particle transport - rolling, saltation and suspension are observed. During simulations the average bed height is monitored and its steady state value is used for proposing a correlation between solids volume fraction ( ϕ ), shear Reynolds number ( Re s ) and Archimedes number ( Ar ). This correlation is used to predict the critical shear Reynolds number for particle lift-off and a condition at which particles would occupy the whole channel at a given Archimedes number. The value of this critical Reynolds number is compared with the critical Reynolds number for single particle lift-off.